Réponses

  • carys
  • Modératrice confirmée
2013-03-09T18:18:16+01:00

(2x - 3) (5x + 2) - (2x - 3) (3x - 5) = 10x² + 4x - 15x - 6 - 6x² + 10x + 9x - 15

                                                         = 4x² + 8x - 21

                                                         = (2x-3)(2x+7)

 

per contre je ne vois pas ce que l'on est censé remarquer dsl :s

2013-03-09T18:20:14+01:00

1. (2x - 3) (5x + 2) - (2x - 3) (3x - 5) = (10x² + 4x - 15x -6) - (6x² - 10x - 9x + 15)

= 10x² - 11x - 6 - 6x² + 19x - 15

= 4x² + 8x - 21

 

2. (2x - 3) ( 5x + 2) - (2x - 3) (3x - 5) = (2x - 3) (5x + 2 - (3x - 5))

= (2x - 3) (5x + 2 - 3x + 5)

= (2x - 3) (2x + 7)

 

3. (2x - 3) (2x + 7) = 4x² + 14x - 6x - 21 = 4x² + 8x - 21

On remarque que c'est égale à la réponse de la question 1.